2019
DOI: 10.1177/0018726719848809
|View full text |Cite
|
Sign up to set email alerts
|

From job crafting to home crafting: A daily diary study among six European countries

Abstract: The actions that individuals take to proactively craft their jobs are important to help create more meaningful and personally enriching work experiences. But do these proactive behaviors have implications beyond working life? Inspired by the suggestion that individuals aim for a meaningful life we examine whether on days when individuals craft their jobs, they are more likely to craft non-work activities. It also seems likely that characteristics of the home environment moderate these cross-domain relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 49 publications
2
84
1
Order By: Relevance
“…Reduce the workload of a voluntary position in a charity organization (volunteer) (Gagnon, 2008) • Time-spatial job crafting o Boundary management styles, individual needs & attitudes (Wessels et al, professionalism (Berger et al, 2017) • Leisure Crafting o Job demands (i.e., avoidance need) when job autonomy was low (Petrou & Bakker, 2016) • Home crafting Home autonomy strengthened the positive association between job crafting and home crafting (Demerouti et al 2019) Crafting Efforts → Needs satisfaction…”
Section: Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduce the workload of a voluntary position in a charity organization (volunteer) (Gagnon, 2008) • Time-spatial job crafting o Boundary management styles, individual needs & attitudes (Wessels et al, professionalism (Berger et al, 2017) • Leisure Crafting o Job demands (i.e., avoidance need) when job autonomy was low (Petrou & Bakker, 2016) • Home crafting Home autonomy strengthened the positive association between job crafting and home crafting (Demerouti et al 2019) Crafting Efforts → Needs satisfaction…”
Section: Relaxationmentioning
confidence: 99%
“…Crafting motives Crafting behaviors and cognitions Domain Outcomes investigated Home crafting (Demerouti et al, 2019) Needs discrepancy (i.e., perceived (mis)fit) Avoidance-focused (reducing demands), Approach-focused (seeking resources, seeking challenges)…”
Section: Conceptual Modelmentioning
confidence: 99%
“…workload) and resources at work and at home (e.g. home autonomy) interact and jointly affect people's sense of meaning (Demerouti et al, 2020;Petrou et al, 2017).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Studies have already shown the beneficial effects of both job crafting-where employees actively reframe their work physically, cognitively, and socially (e.g., Wrzesniewski and Dutton, 2001;Demerouti, 2014;Vogt et al, 2016;Wessels et al, 2019)-and leisure crafting (Petrou and Bakker, 2016;Vogel et al, 2016;Petrou et al, 2017). A recent study by Demerouti et al (2019) suggested that the beneficial implications of job crafting transcend life boundaries, which the authors state have also consequences in terms of experiencing meaning in life.…”
Section: Introductionmentioning
confidence: 99%